Institution for mass psychotherapy - Miklošević, Željka (Array, 2012)
The paper presents the Museum of Broken Relationships in Zagreb, Croatia, and offers a potential redefinition of the nature and the role of the museum and its ‘use’ of material culture in communicating with audiences. The Museum invites people to donate artefacts which represent their former relationships. The collection is thus formed out of need for ‘emotional cleansing’ which might respond to similar and/or opposite needs and wishes of museum visitors. Each donated artefact, mainly a mass product is accompanied by a written explanation. It is through the interpretation of these composite museum objects, formed by texts and artefacts that the visitors identify with or disassociate from the stories told by the objects. The aim of the paper is to explore distinctive features of these objects as private, individual signs within a public context of the museum and to show the processes through which they are created and experienced.